2015
DOI: 10.1007/s00402-015-2361-0
|View full text |Cite|
|
Sign up to set email alerts
|

Fifth metacarpal neck fractures treated with soft wrap/buddy taping compared to reduction and casting: results of a prospective, multicenter, randomized trial

Abstract: This study supports the use of soft wrap and buddy taping for treatment of boxer's fracture with palmar angulation ≤70° and no rotational deformity. Although there was no statistical difference in satisfaction with the esthetic appearance, the patient must be willing to accept the loss of the "knuckle" with this treatment method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…It is well documented that simple buddy-taping and some sort of functional bandage of the hand leaving the MCP joints free yield functional results that are equivalent to those obtained by reduction and immobilization of the MCP joints in a cast (Hansen and Hansen, 1998; Harding et al., 2001; Konradsen et al., 1990; Kuokkanen et al., 1999; Statius Muller et al., 2003; van Aaken et al., 2016). Several studies have even showed that immediate mobilization in the case of metacarpal neck fractures is beneficial for early restoring motion and return to work (Hansen and Hansen, 1998; Harding et al., 2001; Konradsen et al., 1990).…”
Section: Questions Remain For the Future To Seek More Solid Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that simple buddy-taping and some sort of functional bandage of the hand leaving the MCP joints free yield functional results that are equivalent to those obtained by reduction and immobilization of the MCP joints in a cast (Hansen and Hansen, 1998; Harding et al., 2001; Konradsen et al., 1990; Kuokkanen et al., 1999; Statius Muller et al., 2003; van Aaken et al., 2016). Several studies have even showed that immediate mobilization in the case of metacarpal neck fractures is beneficial for early restoring motion and return to work (Hansen and Hansen, 1998; Harding et al., 2001; Konradsen et al., 1990).…”
Section: Questions Remain For the Future To Seek More Solid Evidencementioning
confidence: 99%
“…I also treat almost all fractures of the fifth metacarpal neck with immediate mobilization of the fingers, with buddy-taping of the ring and little fingers, and a functional brace allowing the wrist a free range of motion, an approach supported by published evidence (Hansen and Hansen, 1998; Harding et al., 2001; Konradsen et al., 1990; Kuokkanen et al., 1999; Statius Muller et al., 2003; van Aaken et al., 2016). Problematic malrotation of the little finger occurs extremely rarely.…”
Section: Whether a Cast Or Splinting Is Necessarymentioning
confidence: 99%
“…Although satisfactory clinical results were reported with the application of the traditional UGS splint, it may lead to high patient discomfort due to the limitation of wrist and finger movements [5]. Different functional splinting and soft wrap/bandage treatment methods were described to overcome the patient discomfort and the majority of the studies reported satisfactory outcomes [68]. Acceptable outcomes have also been reported after the treatment of distal and diaphyseal fractures of the fifth metacarpals with a well-molded functional metacarpal splint (FMS), which is less restricting and more comfortable compared with UGS [5, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Fifth metatarsal fractures have also shown to be safely managed without orthopaedic clinic follow up by using a protocol‐driven process at the ED . Simple fifth metacarpal fractures are common injuries seen in FCs and have also been treated satisfactorily with buddy strap or splint without follow up …”
Section: Introductionmentioning
confidence: 99%